2021
DOI: 10.1097/md.0000000000025873
|View full text |Cite
|
Sign up to set email alerts
|

Thermotherapy for knee osteoarthritis

Abstract: Background: Osteoarthritis of the knee is one of the leading causes of pain and disability among adults. Thermotherapy has been widely used to treat knee osteoarthritis. But its efficiency has not been scientifically and methodically evaluated. The aim of this study is to assess the benefits of thermotherapy for people with osteoarthritis of the knee, in terms of pain, stiffness, and physical dysfunction. Methods: Eight databases will be searched from their inception to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Within an outpatient setting, the provision of professional equipment and techniques ensures that patients receive appropriate treatments. Indeed, numerous studies have indicated that specific equipment and techniques are indispensable in expediting the recovery process [ 33 ]. For instance, thermotherapy, as a traditional physical therapy method, has been proven to be exceptionally effective in alleviating pain, enhancing muscle flexibility, and promoting blood circulation [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Within an outpatient setting, the provision of professional equipment and techniques ensures that patients receive appropriate treatments. Indeed, numerous studies have indicated that specific equipment and techniques are indispensable in expediting the recovery process [ 33 ]. For instance, thermotherapy, as a traditional physical therapy method, has been proven to be exceptionally effective in alleviating pain, enhancing muscle flexibility, and promoting blood circulation [ 34 ].…”
Section: Discussionmentioning
confidence: 99%